Innovation in Islamic Religious Education Learning through the Integration of Games and Ice Breakers: An Analysis of Teacher Understanding Studies in Religious Subjects - Mohammad Viktor Farid Hakim; Muhammad Muhammad; S. Ali Jadid Al Idrus (Universitas Muhammadiyah Enrekang, 2024)
Innovation in Islamic Religious Education learning is very important to increase student interest and engagement. Conventional methods are often less able to attract attention, making PAI material seem less relevant. Through innovative approaches such as technology integration, educational games, and ice breakers, PAI learning becomes more interactive and fun, so that students are more motivated and understand the material in depth. This study aims to determine the level of understanding of Islamic Religious Education teachers regarding Islamic religious education learning innovations through the integration of games and ice breakers. This type of research is a type of survey research with a quantitative approach. The population and sample of this study use a random sampling technique that will be given to the subjects using a google form. The results of the survey which was tested with several questions via google form and interviews via zoom meet were given to 50 teachers, as many as 12% of teachers who already understood how to innovate learning through games and ice breakers, but as many as 88% of teachers who still had many difficulties with learning innovations through games and ice breakers. So that the existence of this article can help teachers to be able to understand how to make Islamic religious education learning innovations through the integration of games and ice breakers